The Influence Of Work Dıscıplıne And Work Motıvatıon On The Performance Of State Elementary School Teachers In Kuranjı Dıstrıct, Padang Cıty - Arjunaini Arjunaini; Sulastri Sulastri; Sufyarma Marsidin; Irsyad Irsyad (Cita Konsultindo Research Center, 2024)
Based on initial observations in the field, it appears that the performance of state elementary school teachers in Kuranji District, Padang City is not good. This is thought to be related to work discipline and teacher work motivation, so research is needed to reveal the researchers' initial assumptions. This research aims to determine the influence of work discipline and work motivation on the performance of state elementary school teachers in Kuranji District, Padang City. The hypotheses in this research are: 1) work discipline influences teacher performance, 2) work motivation influences teacher performance, and 3) work discipline and work motivation together influence teacher performance. All state elementary school teachers in Kuranji District, Padang City are the population in this study with a total of 328 people. The sample in this study was 112 people, the sampling technique was the Stratified Proportional Random Sampling technique by looking at the length of service of the teachers. The instruments used in this research were assessment scales and Likert scale model questionnaires. This research was analyzed using correlation and regression techniques. The results of research data analysis show that: 1 work discipline has an effect on teacher performance by 16.6%, 2) work motivation has an effect on teacher performance by 31.4%, and 3) work discipline and work motivation together have an effect on teacher performance by 36%. The teacher performance achievement level score was 89.61% in the good category, for work discipline, it was in the high category with a score of 90.5% while for teacher motivation it was also in the high category with a score of 90.44%. This research implies that work discipline and teacher work motivation are two things that can improve teacher performance even though other factors can influence it.